Modulation of KV7 Channel Deactivation by PI(4,5)P2 - Villalba-Galea, Carlos A. (Frontiers in Pharmacology, 2020)
The activity of KV7 channels critically contributes to the regulation of cellular electrical excitability in many cell types. In the central nervous system, the heteromeric KV7.2/KV7.3 channel is thought to be the chief molecular entity giving rise to M-currents. These K+-currents as so called because they are inhibited by the activation of Gq protein-coupled muscarinic receptors. In general, activation of Gq-protein coupled receptors (GqPCR) decrease the concentration of the phosphoinositide PI(4,5)P2 which is required for KV7 channel activity. It has been recently reported that the deactivation rate of KV7.2/KV7.3 channels decreases as a function of activation. This suggests that the open/activated channel stabilizes as activation persists. This property has been regarded as evidence for the existence of modal behavior in the activity of these channels. In particular, it has been proposed that the heteromeric KV7.2/KV7.3 channel has at least two modes of activity that can be distinguished by both their deactivation kinetics and sensitivity to retigabine. The current study was aimed at understanding the effect of PI(4,5)P2 depletion on the modal behavior of KV7.2/KV7.3 channels. Here, it was hypothesized that depleting the membrane of P(4,5)P2 would hamper the stabilization of the open/activated channel, resulting in higher rates of deactivation of the heteromeric KV7.2/KV7.3 channel. In addressing this question, it was found that the activity-dependent slowdown of the deactivation was not as prominent when channels were co-expressed with the chimeric phosphoinositide-phosphatase Ci-VS-TPIP or when cells were treated with the phosphoinositide kinase inhibitor Wortmannin. Further, it was observed that either of these approaches to deplete PI(4,5)P2 had a higher impact on the kinetic of deactivation following prolonged activation, while having little or no effect when activation was short-lived. Furthermore, it was observed that the action of either Ci-VS-TPIP or Wortmannin reduced the effect of Retigabine on the kinetics of deactivation, having a higher impact when activation was prolonged. These combined observations led to the conclusion that the deactivation kinetic of KV7.2/KV7.3 channels was sensitive to PI(4,5)P2 depletion in an activation-dependent manner, displaying a stronger effect on deactivation following prolonged activation.